Desenvolvimento de microemulsão contendo minoxidil para o tratamento da alopecia - (:unkn) unknown (Universidade Federal do Amazonas, 2017)
The topical treatment usually used to combat hair loss is the daily application of minoxidil lotion (MX) (2 to 5%) directly to the scalp. However, pruritus, dryness, scaling of the scalp and contact dermatitis are adverse effects caused by the presence of propylene glycol and ethanol, constituents of the topical MX solution. The objective of this study was to develop and characterize microemulsion systems containing MX in concentrations equal and superior to those available in the market, free of ethanol and propylene glycol. The selection of the oil phase to compose the microemulsion systems occurred by quantifying the solubilized minoxidil in each oil by UV-vis spectrophotometry. For the selection of the surfactant, cosurfactant and the cosurfactant / surfactant ratio (C / T), it was necessary to construct pseudoternary phase diagrams by the titration method. In the selection of the diagram and the points for the preparation of the formulations, it was prioritized to obtain oil-in-water (O / W) type systems with the lowest possible surfactant / cosurfactant amounts. Another determining factor was the amount of MX incorporated. Each formulation was prepared by adding powdered MX to the microemulsion (ME). All formulations were characterized as droplet size, polydispersity index (PDI), transmittance, pH, zeta potential, refractive index (IR), conductivity, viscosity and amount of drug incorporated. The oleic acid was the oil phase that presented the highest amount of solubilized MX (211 ± 3.57 mg / mL) and was therefore chosen for the construction of the pseudoternary phase diagrams. After the construction and analysis of the diagrams, the Tween® 20 surfactant together with the 1,2-hexanediol co-surfactant were selected in the 1: 1 C / T ratio. In total, six formulations were prepared containing 2, 5, 8, 9 and 10% MX. The droplet size in these formulations ranged from 25.33 to 151.63 nm. The PDI is 0.256 to 0.398, indicating that the droplet distribution is monodisperse. The transmittance varied between 96.8 and 99.6%, and the refractive index, from 1.403 to 1.4551, evidencing the transparent nature of these formulations. The measured pH was between 5.3 and 5.89, compatible with the pH of the scalp and the stability of the MX. The MEs exhibited Newtonian flow with low viscosity average, between 23.27 and 95.16 cP, characteristic of these systems. The use of a nonionic surfactant resulted in a zeta potential near zero (-1.08 to 0.023). Considering that the MEs were obtained with the use of a predominantly hydrophilic surfactant and water content higher than that of oil, all developed formulations were considered as water in oil (A / O) (conductivity 29.8 to 91.8 μS / Cm). The drug content in the formulations ranged from 96.10 to 101.31%, confirming that the MX added to each formulation was effectively solubilized by the microemulsified system. The amount of drug dosed in the formulations was 20.80 to 100.44 mg / mL, which is equivalent respectively to the nominal value of 2 and 5%, which is the concentration of minoxidil found in the commercial formulations, and higher, To 10%. Thanks to the introduction of MX in oleic acid, the removal of propylene glycol and ethanol was possible. The development of formulations without these adjuvants are of great importance for the adhesion of patients who abandon treatment due to the appearance of adverse reactions to these constituents.
Keywords: Minoxidil; Microemulsão; Propilenoglicol; Etanol; Dermatite de contato; CIÊNCIAS DA SAÚDE: FARMÁCIA